Brief Report: Nonfatal Overdose Events Among Persons Who Inject Drugs. (1st July 2017) - Robinson, William T.; Kazbour, Catherine; Nassau, Tanner; Fisher, Kiva; Sheu, Shane; Rivera, Alexis V.; Al-Tayyib, Alia; Glick, Sara Nelson; Braunstein, Sarah; Barak, Narquis; Shinefeld, Jennifer; Poe, Jonathon; et al.
Abstract : Abstract: The rate of drug and opioid overdose deaths in the United States has more than tripled over the past 15 years. The ability to conduct public health surveillance on nonfatal overdoses is limited. The current study used National HIV Behavioral Surveillance (NHBS) data to estimate recent and lifetime history of nonfatal overdose events in persons who inject drugs in 7 cities. Recent and lifetime experience of overdose events ranged from 3% to 20% and from 29% to 63%, respectively. Adapting systems such as NHBS may be useful in responding to and monitoring emergent public health problems such as the overdose epidemic.